Principles for the selection and integration of educational multimedia materials - Tom Boyle (Association for Learning Technology, 1998)
A variety of educational multimedia resources, varying in both type and quality, is now available. The course tutor faces the problem of how to evaluate multimedia artefacts and integrate them into course delivery. This paper sets out a principled framework to guide and inform the choice. The task can be approached from two different directions. The first is technologically driven: we survey the latest developments in multimedia and telematics, and query how we can adapt educational practice. The second line of approach is driven by an educational vision: we establish educational goals and principles, and examine how the technology can help implement these goals. In the early multimedia era, developments have often been driven from the first direction. There has been an opportunistic rush to exploit the new technology which has often led to poor-quality systems. This paper follows the second line of approach. It starts with educational aims and principles and finishes with the technology. The paper develops in this way to emphasize the priority of the issues. In a real decision-making context, the issues have to be considered in parallel in order to match educational principles and technological possibilities.